2009
DOI: 10.1213/ane.0b013e31819e74de
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Preoperative Anxiety in Children: Who Is Most Accurate?

Abstract: Background In this investigation, we sought to assess the ability of pediatric attending anesthesiologists, resident anesthesiologists and mothers to predict anxiety during induction of anesthesia in 2 to 16-year-old children (n=125). Methods Anesthesiologists and mothers provided predictions using a visual analog scale and children's anxiety was assessed using a valid behavior observation tool the Modified Yale Preoperative Anxiety Scale (mYPAS). All mothers were present during anesthetic induction and no c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 11 publications
6
37
2
4
Order By: Relevance
“…Children who were younger and rated as less sociable had higher levels of preoperative anxiety. This finding agrees with past research as children of younger age (1‐6 years) often do not have the coping abilities to handle stressful situations . Furthermore, in past studies it has been found that less sociable children have higher anxiety as they are often uncomfortable in new social situations such as awaiting surgery in the hospital …”
Section: Discussionsupporting
confidence: 91%
“…Children who were younger and rated as less sociable had higher levels of preoperative anxiety. This finding agrees with past research as children of younger age (1‐6 years) often do not have the coping abilities to handle stressful situations . Furthermore, in past studies it has been found that less sociable children have higher anxiety as they are often uncomfortable in new social situations such as awaiting surgery in the hospital …”
Section: Discussionsupporting
confidence: 91%
“…Maternal anxiety was evaluated on leaving the OR using the State-Trait Anxiety Inventory tool. 8 MacLaren et al 8 conducted correlational analyses to determine the association between attending anesthesiologist predictions of child anxiety and actual child anxiety at induction of anesthesia and revealed moderate-to-good predictability (P , .001). Anesthesiologists considered the child's behavior in holding, the age of the child, and temperament when assessing anxiety.…”
Section: Quasi-experimental Studiesmentioning
confidence: 99%
“…This suggests that preoperative teaching strategies must not only be age appropriate, but should take into consideration the child's social adaptability, cognitive ability, and temperament. 8 Routine methods of decreasing preoperative anxiety in children include the use of pharmacological therapies and presence of parents during induction. The routine use of preoperative sedatives to reduce anxiety in pediatric patients may result in increased costs, necessitate additional nursing staff, and increase the need for appropriately equipped bed space in the preoperative holding area.…”
mentioning
confidence: 99%
“…SA may have lasting effects on how patients use the health care system or comply with treatment recommendations [2]. However, SA in children can be difficult to detect and treat [3,4]. For this reason, the American Academy of Pediatrics endorses that health care professionals have a responsibility to address anxiety and create favorable environmental conditions for pediatric patients in the PED setting [5].…”
Section: Introductionmentioning
confidence: 99%